Speech Act Analysis in 'Life is Strange 2' Computer Game - Belev, Vladislav (Univerzita Pardubice, 2023)
The aim of this master thesis is to analyse the use and occurrence of directive, commissive and expressive speech acts in the game Life is Strange 2. The central themes of the game, such as the importance of close relationships, coping with loss, and resistance and conflict, give rise to an abundance of these speech acts. The primary speech act categories are further divided into more specific types and examined, while considering flouting the maxims of Grice's Cooperative Principle and their occurrence within larger units, speech events.
Analýza řečových aktů v počítačové hře Life is Strange 2
Keywords: řečový akt; počítačové hry; konverzace; pragmatika; konverzační maximy; speech act; computer games; conversation; pragmatics; maxims of conversation